he positive role of the administrative judge in the balance between public order and public freedoms - Ali Doohee OdhafA ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The positive role of the administrative judge appears in the balance between public order and public freedoms by protecting the public rights and freedoms of individuals in society, as this role is evidenced by the administrative judge’s exercise of the interpretative or discretionary function granted to him, which has a direct impact on the lives of individuals and their freedoms on the one hand. And the public order on the other hand, because the discretionary power granted by the legislator to the judge enables him in many subjects and issues, and he must take the initiative, so here comes his positive role in understanding and interpreting texts and then applying them.